Product quality, informality, and child labour - Eugenia Fotoniata; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper studies the interactions between the structure of product demand, relative wages, and the allocation of economic activity across two sectors. The agrarian sector produces a homogeneous good and consists of informal firms employing adults and children. The modern sector produces a quality-differentiated product: high-quality varieties are produced by formal firms which employ only adult labour, whereas low-quality varieties are produced by informal firms which employ child labour as well. Differences in tastes and incomes across households generate demand for both high-quality varieties and the low-quality varieties. We find that stricter enforcement of child-labour regulations and increases in minimum wages can have beneficial effects as far as the incidence of child labour and the size of the formal sector are concerned. However, since these policies have undesirable welfare effects among segments of wage-earning households, they may not garner the necessary political support.
Keywords: O11; O17; E26; 330; child labour; informality; product quality; welfare; Kinderarbeit; Mehr-Sektoren-Modell; Produktqualität; Informeller Sektor; Wohlfahrtseffekt; Theorie